Circulating Type I Interferon Levels and COVID-19 Severity: A Systematic Review and Meta-Analysis - da Silva, Rafaela Pires; Gonçalves, João Ismael Budelon; Zanin, Rafael Fernandes; Schuch, Felipe Barreto; de Souza, Ana Paula Duarte (Frontiers in Immunology, 2021)
Coronavirus disease 2019 (COVID-19) is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections, resulting in a range of clinical manifestations and outcomes. Laboratory and immunological alterations have been considered as potential markers of disease severity and clinical evolution. Type I interferons (IFN-I), mainly represented by IFN-α and β, are a group of cytokines with an important function in antiviral responses and have played a complex role in COVID-19. Some studies have demonstrated that IFN-I levels and interferon response is elevated in mild cases, while other studies have noted this in severe cases. The involvement of IFN-I on the pathogenesis and outcomes of SARS-CoV-2 infection remains unclear. In this study, we summarize the available evidence of the association of plasma protein levels of type I IFN with the severity of COVID-19. Methods: The PRISMA checklist guided the reporting of the data. A systematic search of the MEDLINE (PubMed), EMBASE, and Web of Science databases was performed up to March of 2021, looking for articles that evaluated plasma protein levels of IFN-I in mild, severe, or critical COVID-19 patients. Comparative meta-analyses with random effects were performed to compare the standardized mean differences in plasma protein levels of IFN-I of mild versus severe and mild versus critical patients. Meta-regressions were performed to test the moderating role of age, sex, time that the IFN-I was measured, and limit of detection of the assay used in the difference between the means. Results: There was no significant difference in plasma levels of IFN-α when comparing between mild and severe patients (SMD = -0.236, 95% CI -0.645 to 0.173, p = 0.258, I2 = 82.11), nor when comparing between patients mild and critical (SMD = 0.203, 95% CI -0.363 to 0.770, p = 0.481, I2 = 64.06). However, there was a significant difference between healthy individuals and patients with mild disease (SMD = 0.447, 95% CI 0.085 to 0.810, p = 0.016, I2 = 62.89). Conclusion: Peripheral IFN-α cannot be used as a severity marker as it does not determine the clinical status presented by COVID-19 patients.